Pelatihan Fundamental Akuntansi : Langkah Awal Mengelola Keuangan dalam Bisnis - Yusuf, Yulia Yunita; Zaimar, Fina Ruzika; Adriansyah, Adriansyah; Ridha, Achmad; Haruna, Hasisa (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
Abstract:  This community service activity aims to improve basic accounting literacy for Micro, Small, and Medium Enterprises (MSMEs). This training emphasizes understanding the fundamentals of accounting as a foundation in managing business finances. The method of implementing the activity is carried out through interactive lectures, simple transaction recording simulations, and group discussions. The results of the activity show an increase in participants' understanding of the importance of financial recording and basic skills in preparing simple financial reports. It is hoped that this activity will be the first step for MSMEs to manage their business finances in a more orderly and structured manner.